Response Surface Method In-Cooperating Embedded System For Bus Route Optimization - Abdalla, Ahmed N.; Mortaza, Mohamed; Ramdan, Razali; Muhammad, Rauf (2013)
The incessant increment of the population and lack of the reliable bus position notification system in big cities is causing the boost of the privately owned cars, has created major traffic problems. First ever time, Response Surface Methodology (RSM) is adopted in this study to present a new real time intelligent buses notification system using routes' coordinates optimization and wireless mesh network emerged in an embedded design. The von Mises and displacement equation is obtained through RSM and trained to the dedicated controller unit. A mature experimental setup is designed to analyze the equation validation. The result from statistical and experimental analysis using DOE implies that the target to optimize a single route coordinates into one digit representing the bus stop number is achieved by -98%. The outcomes of research as location data minimizing and transmission time reduction has a promised potential for a good and reliable route coordinates optimization.